Sintesis dan Karakterisasi Urea Slow Release Fertilizer (SRF) dengan Matriks Kitosan Termodifikasi PVA/CaCO3 - Yasfin Shafa Nurulisia; Sari Edi Cahyaningrum (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2025)
Urea fertilizer is widely used in the agricultural due to its high content of nitrogen (±46%). However, only 30-40% of nitrogen that is effectively absorbed by plants, while the remainder is lost to the environment. Therefore, the development of SRF offers a potential solution to improve the efficiency utilization of urea fertilizer. In this study, urea based SRF was successfully synthesized using the casting method which is the urea with concentration of 0, 1000, 2000 and 3000 ppm was coated with chitosan which modified by PVA/CaCO3. In addition to synthesis, the urea SRF was also characterized through swelling and porosity test showed that the higher the concentration of urea that added, the lower of swelling degree and %porosity of the urea SRF. Meanwhile, the result of the urea release test indicated that when the urea concentration increased led to a higher urea release rate, resulting in a greater percentage of urea release.